Pendidikan Spiritual dalam Kegiatan Pembelajaran Thariqah Syathoriyah Ponpes Fathul ‘Ulum Gandusari Kuwarasan Kebumen - Efendi, Gunawan (Educreative : Jurnal Pendidikan Kreativitas Anak, 2020)
Spiritual based education is defined as a concept, an education system that emphasizes the development of spiritual or spiritual abilities with spiritual standards that can be felt by students to achieve the perfection of life according to Islamic standards. The results of spiritual education research in learning activities of the Tariqah Syathoriyah Ponpes Fathul ‘Ulum Gandusari Kuwarasan Kebumen carried out in various activities namely; selasanan, sulukan, khaul, bai'at, and dhikr. With several methods used, including: riyadhah, discovery (tafakur), tazkiyat an-nafs, and remembrance. And spiritual education carried out by the Syarimah Tariqa congregation includes: honesty, responsibility, discipline, and fairness.